Selected Aspects of Analyses of Failure Rates of Active Safety Systems in Buses - Pawel Drozdziel; Leszek Krzywonos; Radovan Madlenak; Iwona Rybicka (Communications - Scientific letters of the University of Zilina, 2014)
The article outlines the methodology of statistical analysis of failure rate of active safety systems in buses. The theoretical discussion is illustrated with calculations carried out on the basis of empirical data covering a four-year period of operation of selected models of buses at the Motor Transport Company „Wschod“ plc in Lublin (Poland). It was found that the distribution of distances travelled by the analyzed vehicles between successive repairs can be approximated by an exponential distribution